1997
DOI: 10.1111/j.1432-1033.1997.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Spectroscopic and Structural Investigation of the Substrate‐Binding Site in Ascorbate Peroxidase

Abstract: The interaction of recombinant ascorbate peroxidase (APX) with its physiological substrate, ascorbate, has been studied by electronic and NMR spectroscopies, and by phenylhydrazine-modification experiments. The binding interaction for the cyanide-bound derivative (APX-CN) is consistent with a 1 : 1 stoichiometry and is characterised by an equilibrium dissociation binding constant, Kd, of 11.6 t 0.4 pM (pH 7.002, p = 0.10 M, 25.0OC). Individual distances between the non-exchangeable substrate protons of APX-CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 84 publications
(52 reference statements)
7
35
0
Order By: Relevance
“…1 mmol l −1 (Shigeoka et al, 2002). However, a structural study by Hill et al (Hill et al, 1997) showed that APX had a binding (dissociation) constant to the enzyme of K d =11.6 μmol l −1 and it is entirely reasonable that APX was inhibited in our experiments.…”
Section: The Effect Of Calvin-benson Cycle Inhibition On Coral Bleachingmentioning
confidence: 52%
“…1 mmol l −1 (Shigeoka et al, 2002). However, a structural study by Hill et al (Hill et al, 1997) showed that APX had a binding (dissociation) constant to the enzyme of K d =11.6 μmol l −1 and it is entirely reasonable that APX was inhibited in our experiments.…”
Section: The Effect Of Calvin-benson Cycle Inhibition On Coral Bleachingmentioning
confidence: 52%
“…Enzyme purity was additionally assessed using SDS/PAGE, and the preparations were judged to be homogeneous by the observation of a single band on a Coomassie Blue‐stained reducing SDS/polyacrylamide gel. Enzyme concentrations (pH 7.0, µ = 0.10 m , 25.0 °C) were determined using the pyridine haemochromagen method [39]: absorption coefficients were ε 403 = 88 m m −1 ·cm −1 for rAPX [40], ε 397 = 83 m m −1 ·cm −1 for H42A and ε 404 = 95 m m −1 ·cm −1 for H42E.…”
Section: Methodsmentioning
confidence: 99%
“…The domains are connected via helix E. On the basis of the results from nuclear magnetic resonance and computer-modeling, the ascorbate-binding site has been proposed to be in a pocket formed by the heme molecule and the domain I. 6) On the basis of enzyme characteristics and amino acid sequences, APXs of higher plants have been divided into several isoforms; 7) two soluble isoforms in the cytosol and the stroma, and two membranebound isoforms localized in the thylakoids and the microbodies (glyoxysome and peroxisome). Theˆfth isoform, the subcellular localization of which remains unknown, has also been found.…”
mentioning
confidence: 99%